Pengaruh Motivasi, Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai Kantor DPM - Anintiyas, Petrin Dwi; Tjahyanti, Setia (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study was to determine the effect of motivation, compensation and work environment on employee job satisfaction of Office DPM. The population used in this study are employees of Office DPM totaled 98 employees. This study used purposive sampling, namely a sampling technique with certain considerations. The sample in this study were 55 employees. Data collection techniques were carried out by distributing questionnaires to all respondents using a Likert scale measurements. The method for data analysis in this study is multiple linear regression. The results of the analysis of this study indicate that motivation, compensation, and work environment have a positive effect on employee job satisfaction of Office DPM.